Government and rural transformation: Role of public spending and policies in Bangladesh - Mudahar, Mohinder S.; Ahmed, Raisuddin (University Press, 2010)
The British finally granted independence to India in 1947 but the British India was divided into two independent states, India and Pakistan, in the acrimonious process of granting independence. Twenty four years after this landmark episode, another dramatic episode occurred in 1971 in the sub-continent's history that saw the emergence of another independent state, the People's Republic of Bangladesh. The same people, who played a vigorous role in the struggle for Pakistan, became desperate to separate from West Pakistan to emerge as an independent nation. Even though the population of East Pakistan was larger than the population of West Pakistan, usurpation of political power by the West through military and dictatorial governments resulted in egregious economic discriminations against the people of East Pakistan. The average per capita income in East Pakistan in 1948-50 was only about 3 percent lower than per capita income in West Pakistan. The income of the people of Bangladesh was stagnant during the Pakistani era. Poverty was widespread. The war of independence caused extensive damage to infrastructure and interrupted economic relations. Poverty level further widened as well as deepened. People, who did not sympathies with the emergence of Bangladesh as an independent country, expressed explicit as well as implicit doubt on the viability of this new country. This book provides an analysis of long-term transformation of the e c o n o m y, particularly for agriculture and rural development, since independence. Thus the book fills a gap arising from the change in planning approach and enables Bangladesh to look at transformation during the last 3 decades and develop a vision for the coming decades in the area of agriculture and rural development. Past progress has been phenomenal, particularly when viewed within the background of dismal initial conditions. But, though the general direction of policies has been right, there are many deficiencies in the areas of institutional, infrastructural, technological, and political developments. The progress would have been even faster without these deficiencies. However, what matters now are the future prospects if these deficiencies are not corrected in the coming years. Bangladesh is at the crossroad of the trajectory towards the status of a middle-income economy. Without the corrective measures at this stage, the possibility of economy missing the upward trajectory is very real.